"Would you like to listen or not?" : a dissertation which explores the relationship between research participants and anthropologists in Karimpur : a dissertation presented in partial fulfilment of requirements for the degree of PhD in Social Anthropology at Massey University - Rudge, Amanda Jane (Massey University, 1997)
This dissertation explores the relationship between anthropologists and people who live in Karimpur, a north Indian village situated on the Ganges plain, 120 kilometres east of Agra. Karimpur is an anthropological pseudonym for "one of the most studied communities in South Asia" (Wadley 1994:xviii) which has been researched by anthropologists for over seventy years. As a result of this history, the village is currently the subject of four PhD dissertations, one MA thesis, six monographs and over fifty articles and conference papers. This dissertation concludes that an experience of living in such a well researched community has had an effect on the way people relate to the anthropologists who work in Karimpur. While the villagers referred to these researchers as fictive kin, a majority didn't treat them as family but as respected guests. People positioned anthropologists in a fictive jati, or caste, of their own, and had an expectation that they will 'help' them by giving them clothing, money, and medicine in return for the information they gave them. However, few of the people spoken to were aware that the anthropologists who conduct research in their community also write about them. Future research must therefore take account of the villagers' need to read what has been written about them, but it must also address their desire to comment on that work. It is suggested that anthropologists engage in a dialogue with the villagers about what research currently does and what it might do in the future, and that people in Karimpur work with these anthropologists to devise a research policy which addresses their needs for representation.
Keywords: Karimpur, India; Anthropologists; Field work; Anthropological research; Research subjects